Charting shifts and moving forward in abnormal times: An interview with Nancy Fraser - Julia Sichieri Moura (Ethic@: an International Journal for Moral Philosophy)
In this interview Nancy Fraser elucidates important conceptual topics of her theory, she also shares her analysis of the global financial crisis and how it has changed the setting for theorists of justice. Her account reminds us of critical theory’s important role in helping us think - and act – differently in difficult times.